Vagus Nerve Stimulation in Treatment-Resistant Depression: A Case Series of Long-Term Follow-up. Issue 1 (7th March 2023) - Pigato, Giorgio; Rosson, Stella; Bresolin, Nicola; Toffanin, Tommaso; Sambataro, Fabio; Olivo, Daniele; Perini, Giulia; Causin, Francesco; Denaro, Luca; Landi, Andrea; D'Avella, Domenico
Abstract : Objectives: Vagus nerve stimulation (VNS) has been shown to be effective for treatment-resistant depression (TRD). However, long-term (>5 years) studies on the efficacy and tolerability of this treatment have been lacking. Here, we report a long-term clinical follow-up of 5 patients with severe and long-standing TRD, who received a VNS implant. Methods: Of the initial 6 patients with TRD implanted with VNS at our center, 5 of them were followed for 6 to 12 years after implantation. Primary efficacy outcomes were clinical response and improved functioning at follow-up visits. The primary safety outcome was all-cause discontinuation, and the secondary safety outcomes were the number and the severity of adverse events. Results: The VNS implant was associated with a sustained response (>10 years) in terms of clinical response and social, occupational, and psychological functioning in 3 patients. Two patients dropped out after 6 and 7 years of treatment, respectively. Vagus nerve stimulation was well tolerated by all patients, who reported only mild adverse effects. One patient, who discontinued concomitant drug treatment, had a hypomanic episode in the 10th year of treatment. The parameters of the VNS device were fine-tuned when life stressors or symptom exacerbation occurred. Conclusions: Our case series showed that VNS can have long-term and durable effectiveness in patients with severe multiepisode chronic depression, and this could be associated with its neuroplastic effects in the hippocampus. In light of good general tolerability, our findings support VNS as a viable treatment option for TRD.